Flavonoids from Chionanthus retusus (Oleaceae) Flowers and Their Protective Effects against Glutamate-Induced Cell Toxicity in HT22 Cells - Lee, Yeong-Geun (Int J Mol Sci, 2019)
The dried flowers of Chionanthus retusus were extracted with 80% MeOH, and the concentrate was divided into EtOAc, n-BuOH, and H(2)O fractions. Repeated SiO(2), octadecyl SiO(2) (ODS), and Sephadex LH-20 column chromatography of the EtOAc fraction led to the isolation of four flavonols (1–4), three flavones (5–7), four flavanonols (8–11), and one flavanone (12), which were identified based on extensive analysis of various spectroscopic data. Flavonoids 4–6 and 8–11 were isolated from the flowers of C. retusus for the first time in this study. Flavonoids 1, 2, 5, 6, 8, and 10–12 significantly inhibited NO production in RAW 264.7 cells stimulated by lipopolysaccharide (LPS) and glutamate-induced cell toxicity and effectively increased HO-1 protein expression in mouse hippocampal HT22 cells. Flavonoids with significant neuroprotective activity were also found to recover oxidative-stress-induced cell damage by increasing HO-1 protein expression. This article demonstrates that flavonoids from C. retusus flowers have significant potential as therapeutic materials in inflammation and neurodisease.